miR-126 and miR-126*: New Players in Cancer - Jeannette Meister; Mirko H. H. Schmidt (The Scientific World Journal)
Cancer progression is characterized by autarky in growth signals, insensitivity to growth-restrictive signals, evasion of apoptosis, a limitless potential to replicate, sustained angiogenesis, and tissue invasion, including metastasis. The regulation of these cellular processes relies on a fine-tuned control of molecular signal cascades. In recent years, short noncoding RNAs termed microRNAs (miRNAs) have been described as a novel class of molecular regulators. These affect various signaling cascades during the progression of neoplastic diseases by the regulation of gene expression on the post-transcriptional level. The novel endothelial cell–derived secreted protein epidermal growth factor–like domain 7 (EGFL7) has been suggested to control vascular tubulogenesis. Further, the two biologically active miRNAs miR-126 and its complement miR-126*, which are encoded by intron 7 of the egfl7 gene, have been described to mediate vascular functions. Knock-out studies in zebrafish and mice suggested a major role of miR-126 in angiogenesis and vascular integrity, which was mediated by the repression of inhibitors of VEGF-induced proliferation in endothelial cells. Recent studies revealed the distribution and function of miR-126 and miR-126* in various types of cancer, and assigned a role to both miRNAs as suppressors of tumor formation. Indeed, miR-126 and miR-126* have been reported to impair cancer progression through signaling pathways that control tumor cell proliferation, migration, invasion, and survival. Conversely, miR-126 and miR-126* may have a supportive role in the progression of cancer as well, which might be mediated by the promotion of blood vessel growth and inflammation. In this work, we will summarize the current knowledge on functions of miR-126/miR-126* that are relevant for cancer formation, and we will discuss their potential clinical use as predictive markers of survival and application as novel therapeutic targets for the treatment of neoplastic diseases.